POLA BEHAVIOUR REWARD DAN PUNISHMENT - Eva Maghfiroh (Institut Agama Islam Syarifuddin Lumajang, 2020)
Aggressive behavior is a form of behavior that can hurt other people. This behaviourcomes from cognitive processes that are disrupted. Students, in Islamic boarding school,who experience aggressive behavior, can become aggressive too. This article discusseshow teachers deal with students with aggressive behavior in Islamic boarding school. Oneof the ways, is to provide reward and punishment for them, who have aggrescive behavior.Aggressive behavior should not interfere with the growth and development of students.